2009
DOI: 10.3748/wjg.15.3283
|View full text |Cite
|
Sign up to set email alerts
|

Is ERCP really necessary in case of suspected spontaneous passage of bile duct stones?

Abstract: AIM:To investigate the usefulness of magnetic resonance cholangiopancreatography (MRCP) and the need for endoscopic retrograde cholangiopancreatography (ERCP) in cases of suspected spontaneous passage of stones into the common bile duct. METHODS:Thirty-six patients with gallbladder stones were clinically suspected of spontaneous passage of stones into the common bile duct because they presented with clinical symptoms such as abdominal pain and fever, and showed signs of inflammatory reaction and marked rise of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
2
14
0
2
Order By: Relevance
“…Some studies suggested that performing MRCP first in patients have improved clinical and hematological parameters. If the stone has spontaneously passed, it would reduce the exposure of ERCP and complication due to ERCP [ 10 , 20 ]. Our study found that post-ERCP pancreatitis was 21.1% in spontaneous CBD stone passage.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that performing MRCP first in patients have improved clinical and hematological parameters. If the stone has spontaneously passed, it would reduce the exposure of ERCP and complication due to ERCP [ 10 , 20 ]. Our study found that post-ERCP pancreatitis was 21.1% in spontaneous CBD stone passage.…”
Section: Discussionmentioning
confidence: 99%
“…Post-ERCP pancreatitis (PEP) is one of the most serious complications of ERCP. In recent years, computed tomography and/or magnetic resonance cholangiopancreatography (MRCP) have become more highly applicable diagnostic approaches for pancreatic and biliary system diseases than ERCP [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that stones were spontaneously eliminated in 2 patients among the patients with bile duct stone in the present study, moreover, since attainment to the papilla and subsequent treatment are more difficult in the patients with Billroth II-reconstructed stomach than usual patients, it may be better to perform MRCP at first and then to follow-up the patients without conducting the ERCP, as much as possible, if no stone is identified[28-30]. The treatment with endoscope on biliopancreatic disease in the patients with Billroth II-reconstructed stomach is less invasive, which is considered the treatment to be tried at first.…”
Section: Discussionmentioning
confidence: 99%